Kajian Tentang Pemasaran Online Untuk Meningkatkan Peluang Bisnis - Amiruddin Amiruddin; Listia Muslimah; Endang Dwi Amperawati (Amal Insani Foundation, 2023)
This research aims to examine online marketing to promote brands, build preferences and increase sales through various online marketing. This research is a survey, with sources being Postgraduate Students with Masters of Management at Primagraha University who have online-based independent creative businesses for the 2022-2023 academic year. The results of the observations found various kinds of products/services with several business names, such as Ksatria Graphic, MultiqRaft, Acharehe hockey, Anugrah Sentosa, Rumah Showcase, and many more. This research provides an overview of the basis for selecting media, strategies, selecting segments, strengths, and weaknesses, and what failures have been experienced in running a business. The desired hope from the results of this research is to become a reference for potential actors, especially young people, in online marketing. In the future, we can complement an excellent example into a more robust strategy.